Ameliorative efficacy of bioencapsulated Chironomous larvae with Shilajit on Zebrafish (Danio rerio) exposed to Ionizing radiation. (October 2017) - Musthafa, M. Saiyad; Athaullah, A.; Anbumani, S.; Ali, A. Jawahar; War, Mehrajuddin; Paray, Bilal Ahmad; Al-Sadoon, Mohammad K.; Muthiah, S.S.; Kembeeram, Palani; Harikrishnan, R.
Abstract: Using Zebrafish ( Danio rerio ) as a model organism, we evaluated the radioprotective and antioxidant effects of the Indian traditional medicine Shilajit exposed to X-Ray. The Zebrafish were divided into three experimental groups and control group, each group containing ten fish. The three experimental fish groups, group I, group II and group III were fed with 3, 5 and 7 ppm shilajit encapsulated Chironomous larvae and group IV served as a control fed with non- encapsulated larvae. After 60 days of feeding trial, fish were irradiated with X-Ray at a single acute dose of 1 Gy. 72 h of post-irradiation, each experimental fish were observed for its morphological, behavioral, clinical symptoms, antioxidant levels and DNA damage were evaluated. Among the experimental groups 5 ppm shilajit encapsulated Chironomous larvae fed fish group shows the most significant radioprotective effects compared with control and other experimental fish groups. The present study indicates that shilajit have significant radioprotective and antioxidant enhancing capability. The humus substance of shilajit may be the factor responsible to react with radiation-derived or radiation related reactive species on zebrafish. Highlights: Radioprotective effects of Shilajit were evaluated using Zebrafish. Zebrafish exposed with X-Ray at a single acute dose of 1 Gy. Morphological, behavioral and clinical pathology were assessed. Antioxidant levels and DNA damage were assessed. Shilajit have significant radioprotective and antioxidant enhancing capability.